Altered glucocorticoid metabolism represents a feature of macroph‐aging. Issue 6 (28th May 2020) - Valbuena Perez, Jenny Vanessa; Linnenberger, Rebecca; Dembek, Anna; Bruscoli, Stefano; Riccardi, Carlo; Schulz, Marcel H.; Meyer, Markus R.; Kiemer, Alexandra K.; Hoppstädter, Jessica
Abstract: The aging process is characterized by a chronic, low‐grade inflammatory state, termed "inflammaging." It has been suggested that macrophage activation plays a key role in the induction and maintenance of this state. In the present study, we aimed to elucidate the mechanisms responsible for aging‐associated changes in the myeloid compartment of mice. The aging phenotype, characterized by elevated cytokine production, was associated with a dysfunction of the hypothalamic–pituitary–adrenal (HPA) axis and diminished serum corticosteroid levels. In particular, the concentration of corticosterone, the major active glucocorticoid in rodents, was decreased. This could be explained by an impaired expression and activity of 11β‐hydroxysteroid dehydrogenase type 1 (11β‐HSD1), an enzyme that determines the extent of cellular glucocorticoid responses by reducing the corticosteroids cortisone/11‐dehydrocorticosterone to their active forms cortisol/corticosterone, in aged macrophages and peripheral leukocytes. These changes were accompanied by a downregulation of the glucocorticoid receptor target gene glucocorticoid‐induced leucine zipper (GILZ) in vitro and in vivo. Since GILZ plays a central role in macrophage activation, we hypothesized that the loss of GILZ contributed to the process of macroph‐aging. The phenotype of macrophages from aged mice was indeed mimicked in young GILZ knockout mice. In summary, the current study provides insight into the role of glucocorticoid metabolism and GILZ regulation during aging. Abstract : The present study examined the age‐associated changes in glucocorticoid metabolism in macrophages in order to improve the current understanding of "inflammaging."